2012
DOI: 10.2174/1745017901208010091
|View full text |Cite
|
Sign up to set email alerts
|

Victimization and PTSD in A Rural Kenyan Youth Sample

Abstract: Within the last ten years, there has been a growing number of epidemiological studies, examining the effect of trauma exposure in children and adolescents. Although studies concerning Post-traumatic Stress Disorder (PTSD) have been conducted in a wide array of different cultural contexts [1], the knowledge on traumatization and development of PTSD is still limited [2]. Most studies conducted are clinical studies, which deal with subjects that have already been traumatized or affected by specific single events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 43 publications
4
33
2
Order By: Relevance
“…parental divorce or being bullied), and the prevalence of PTSD among Ugandan senior 3 rd year students. The study replicates previous European studies of the same age groups [7]- [10], one Indian study [13], and one Kenyan Study [5].…”
Section: Victimization and Ptsd In Ugandan Youthsupporting
confidence: 84%
See 1 more Smart Citation
“…parental divorce or being bullied), and the prevalence of PTSD among Ugandan senior 3 rd year students. The study replicates previous European studies of the same age groups [7]- [10], one Indian study [13], and one Kenyan Study [5].…”
Section: Victimization and Ptsd In Ugandan Youthsupporting
confidence: 84%
“…Karsberg & Elklit [5] conducted a study in rural Kenya among 477 secondary school students with a mean age of 16.4 years. A total of 34.5% met diagnostic criteria for PTSD, with 30.5% of boys and 42.3% of girls meeting PTSD criteria.…”
Section: Victimization and Ptsd In Ugandan Youthmentioning
confidence: 99%
“…Similarly, other studies conducted in rural Kenya among secondary school students found higher prevalence of PTSD at 34.5% conducted in Central and Northern Kenya (also using the HTQ [6]. In another study among students in 49 public secondary schools located in urban and rural areas, 50.5% met full criteria (criteria A-E were met in DSM-IV-R for PTSD) and 34.8% met partial criteria (1 symptom was checked in each DSM-IV symptom criterion) using the Child PTSD checklist [13].…”
Section: Discussionsupporting
confidence: 56%
“…The cut off for the presence of PTSD symptoms was set at a mean score greater than > 2.5 [18]. The HTQ was successfully used in a prior study in Kenya with an internal consistency of Cronbach's α =.75 [6]. The reliability of HTQ in the present study was Cronbach's α =.83.…”
Section: Ptsdmentioning
confidence: 88%
See 1 more Smart Citation